Very low emissions of airborne particulate pollutants measured from two municipal solid waste incineration plants in Switzerland. (October 2017) - Setyan, Ari; Patrick, Michael; Wang, Jing
Abstract: A field campaign has been performed in two municipal solid waste incineration (MSWI) plants in Switzerland, at Hinwil (ZH) and Giubiasco (TI). The aim was to measure airborne pollutants at different locations of the abatement systems (including those released from the stacks into the atmosphere) and at a near-field (∼1 km) downwind site, in order to assess the efficiency of the abatement systems and the environmental impact of these plants. During this study, we measured the particle number concentration with a condensation particle counter (CPC), and the size distribution with a scanning mobility particle sizer (SMPS) and an aerodynamic particle sizer (APS). We also sampled particles on filters for subsequent analyses of the morphology, size and elemental composition with a scanning electron microscope coupled to an energy dispersive X-ray spectroscope (SEM/EDX), and of water soluble ions by ion chromatography (IC). Finally, volatile organic compounds (VOCs) were sampled on adsorbing cartridges and analyzed by thermal desorption-gas chromatography/mass spectrometry (TD-GC/MS), and a portable gas analyzer was used to monitor NO, SO2, CO, CO2, and O2 . The particle concentration decreased significantly at two locations of the plants: at the electrostatic precipitator and the bag-house filter. The particle concentrations measured at the stacks were very low (<100 #/cm 3 ), stressing the efficiency of the abatement system of the two plants. At Hinwil, particles sampled at the stack were mainly constituted of NaCl and KCl, two salts known to be involved in the corrosion process in incinerators. At Giubiasco, no significant differences were observed for the morphology and chemical composition of the particles collected in the ambient background and at the downwind site, suggesting that the incineration plant released very limited amounts of particles to the surrounding areas. Graphical abstract: Highlights: Pollutants emitted by two municipal solid waste incineration plants were measured. Electrostatic precipitators and bag-house filters removed >99% of particles. Particles released at the stacks were mainly NaCl and KCl (corrosive salts). The particle concentrations at the stacks were very low (<100#/cm 3 ).